Penerapan Media Pembelajaran Berbasis Teknologi dan Model Team Games Tournament Pada Muatan Pembelajaran PPKn - Fajar Aunurofiq; Saifuloh Annaafi; Faizah F; Nur Indah Wahyuni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to increase enthusiasm and motivation as well as the level of understanding which can have an impact on the learning outcomes of class IV students at SD Negeri 5 Krajankulon in Civics learning content on cultural diversity material in the surrounding environment with technology-based media, including presentation media and interactive learning videos as well as evaluation tools Quizizz Paper Mode and applies the Team Games Tournament learning model. The research was conducted at SD Negeri 5 Krajankulon, Kaliwungu, Kendal. The population in this study were all 4th grade students at SD Negeri 5 Krajankulon. This research uses a qualitative descriptive research method to describe the circumstances or conditions of the class related to the level of students' understanding and enthusiasm in real Civics learning. At the evaluation stage, tests (quizzes) are carried out through the Quizizz application to see the level of understanding through student learning outcomes. Based on the research that has been carried out, students have worked on the questions that have been provided and obtained scores that meet the minimum standards for completeness. It can be concluded that the application of technology-based media and tournament-based learning models can increase enthusiasm and motivation as well as student learning outcomes in Civics learning.